Svalbard's Record‐Breaking Arctic Summer 2024: Anomalies Beyond Climatological Warming Trends - Daan van denBroek; Gabin H. Urbancic; Mika Rantanen; Timo Vihma (Geophysical Research Letters)
Abstract The Svalbard archipelago region is one of the fastest warming regions in the world. The majority of warming has occurred in wintertime, although the summer season has also been warming approximately linearly since 1980. Nevertheless, in recent years, many monthly and seasonal temperature records have been set in summer, with 2024 breaking its mean summer and August temperature records by the largest margins in the measurement history. In this study, we examine 2024s temperature extremes. The mean August temperature stands out as falling outside of the climatological distribution even after accounting for the warming trend. Our findings suggest that 2024s records are a result of an unprecedented combination of persistent atmospheric patterns and interaction with the warming seas. Given the exceptional nature of these temperature extremes, we recommend further research to the potential increase in the persistence of weather and the consequences of associated temperature extremes.